1991
DOI: 10.1017/s0033822200013278
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dates for Lava Flows and Pyroclastic Deposits on São Miguel, Azores

Abstract: We report 63 new radiocarbon analyses of samples from São Miguel, the largest (ca 62 × 13km) and most populous (ca 150,000 inhabitants) island in the Azores archipelago (Fig 1). The samples are mainly carbonized tree roots and other plant material collected from beneath 20 mafic lava flows and spatter deposits and from within and beneath 42 trachytic pyroclastic flow, pyroclastic surge, mudflow, pumice-fall, and lacustrine deposits and lava flows. One calcite date is reported. The samples were collected during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 7 publications
0
51
0
Order By: Relevance
“…The products of this eruption were dated at 0.840 + 0.060 ka BP (Moore & Rubin 1991). P17 is the only deposit that covers Pico das Camarinhas and its dating confirms the stratigraphy, namely, that little time elapsed between the eruption of these two eruptive events.…”
Section: Flank Eruptionsmentioning
confidence: 63%
See 1 more Smart Citation
“…The products of this eruption were dated at 0.840 + 0.060 ka BP (Moore & Rubin 1991). P17 is the only deposit that covers Pico das Camarinhas and its dating confirms the stratigraphy, namely, that little time elapsed between the eruption of these two eruptive events.…”
Section: Flank Eruptionsmentioning
confidence: 63%
“…The stratigraphic system proposed for the volcano by Moore is based on the identification of an eruptive sequence formed by pyroclastic flows (locally welded), fall and surge deposits, named the 'outflow deposit', which he considered to be linked to caldera formation c. 22 ka ago. This age was set by taking into account the carbon dating of charcoal found in deposits located two palaeosols above the 'outflow deposit', which gave an age of 21.160 + 0.180 ka BP (Moore & Rubin 1991). This does not agree with the absolute dating established in Queiroz (1997).…”
Section: Genesis Of the Calderamentioning
confidence: 96%
“…(e.g. Moore and Rubin 1991;Wallenstein 1999;Pensa et al 2015), but its age is generally reported as ~5 ka. Although the deposit is not genetically related to Furnas, it is well known and easily identified and, in the absence of well-exposed deposits relating to the second caldera-forming event at Furnas (~12,000 14 C y B.P.…”
Section: Furnas Eruptive Historymentioning
confidence: 99%
“…Previous detailed geological mapping and radiocarbon dating provide an excellent guide to eruption chronology on São Miguel (Booth et al, 1978;Moore, 1990; Moore and Rubin, 1991). Only the most easterly vol- Table 1.…”
Section: Geological Background and Sampling Strategymentioning
confidence: 99%